SURVEI KELUARGA SEHAT DI DESA PENEGAH KECAMATAN PELAWAN - Tina Yuli Fatmawati (Universitas Baiturrahim, 2019)
The movement of healthy living people is a choice in realizing a better degree of public health. The aim is to increase awareness in the community in preventing disease. Health problems that aries are the result of unhealthy living behaviors and poor environmental sanitation. This research is a descriptive research that is a study directed to describe or describe a situation within a community or society. The sample in this study were 277 Famillies in Penegah village with total sampling technique. The results is majority of mothers using family planning, mothers giving birth in health care facilities, babies receiving 100% complete immunization, the majority of mothers giving exclusive breastfeeding, The people not found pulmonary tuberculosis, 100% of hypertensive patients checking periodically, no one suffering from mental disorders, the majority of families there are those who smoke, the majority of families use health insurance / BPJS, the coverage of monitoring for toddlers' growth is 100%, the use of clean water sources and 100% healthy latrines. It is expected that the Puskesmas will further encourage the independence of healthy life for individuals, families, groups and communities through community empowerment so that it becomes a healthy community.